FOREIGN POSTGRADUATE STUDENTS AND THE ONLINE CATALOGUE AT THE UNIVERSITY OF MALAYA LIBRARY - P. G., Ariyapala; N.N., Edzan (Malaysian Journal of Library and Information Science, 2002)
Describes a study, which investigates the Online Public Access Catalogue (OPAC ) use behavior of foreign postgraduate students at the University of Malaya Library. This involves their ability to use OPAC, their knowledge about OPAC, and the reasons for the effective use of OPAC. The results indicate that most of the students from developing countries possess various levels of OPAC use abilities. Most indicate that there are no OPAC facilities in their home countries, and if available, it is limited to university libraries. OPAC searches are mainly for title, subject, author/title keyword, and author. Title searches are the most frequently used. Students using the University of Malaya Library indicate that the OPAC is relatively easy to use but students are moderately successful in locating items. Students selftrained themselves when using the OPAC. Most did not receive any training or learnt it from the Library and for those who attended the training programme, the majority of them noted that it has been successful. Most of the students are generally unaware of other facilities that are available in the OPAC.